Intra- and inter-rater reproducibility of ultrasound imaging of patellar and quadriceps tendons in critically ill patients - Castro, Joana (2019)
Since the outset of body image reconstruction for diagnosis purposes, ultrasound has been used to investigate structural changes located in tendons. Ultrasound has clinical applications in the intensive care unit, but its utility for tendon imaging remains unknown. Thus, we aimed to determine intra- and inter-rater reproducibility of measures obtained by images generated through morphological tendon sonographic analysis recorded from critically ill patients. We designed a cross-sectional study to assess thickness, cross-sectional area, and echogenicity of patellar and quadriceps tendons in a convenience sample formed with 20 critically ill patients. Two independent raters (experienced and novice) recorded repeated measures, checking for agreement (Kappa statistics) and reliability (Intraclass coefficient Correlation-ICC and Bland-Altman). The quality of images acquired by the two independent raters substantially agreed (k = 0.571–1.000), regardless of the region on the patellar tendon or the studied tendon (patellar or quadriceps). Regardless of how much experience the rater had, their repeated records (intra-rater reliability) always demonstrated almost complete correlation, ICC ranging from 0.89 to 0.98 for both tendons in all outcomes. At the same way, the statistically significant inter-rater ICC ranging from 0.87 to 0.97. Both repeated measures by the raters (intra-rater) and the repeated single and double measures between the raters (inter-rater) presented a minimum measurement error constituting a predominant pattern of random variability. We conclude that ultrasound imaging acquisition performed by independent raters for tendon thickness, CSA, and echogenicity monitoring of critically ill patients are acceptable and are not influenced by rater experience.